Aspectos linguístico-ergonômicos em rótulos: avaliação da linguagem verbo-visual de rótulos de embalagens para alimentos achocolatados - Costa, Gildete Fernandes da (2011)
We have been living in a world of packed products. The package and the labels support the companies to communicate with the customers in addition to give protection, storage and convenience in proportion to the products that move in the price list. The labels mainly add up a value which helps the companies differ their products and increase the value of the brands among the final customers. However, the information given in the label are not clear sometimes. It displays a verbal-visual defective language resulted from a poor visibility, legibleness and comprehensibleness of the verbal and visual marks. The aim of this research is to verify, according to the costumers‟ view, the level of the clarity in the informative texts, harmony and ergonomic conformity of the package labels in the chocolate powder of the Claralate brand, considering the linguistic aspects presented on the labels. The criteria to evaluate the chocolate package selected were based on the linguistic field: the organization and the structure of the text derided from the classification of the textual genre; the clarity and the comprehension of the language utilized on those labels. From the ergonomic view, the informative and ergonomic conformity, based on the following requirements: legibility, symbols, characters, reading fields and intermission of the written lines. Therefore, the research done july 2007 and added july 2011 had a structured questionnaire in the interview put to the 118 customers of the chocolate package that go shopping in one of the two supermarkets in Floriano, Piauí São Jorge and/or Super Quaresma. The main results of the investigation show that the linguistic aspects in the informative texts of the labels provide the customers‟ expectancy partially, while the consideration of the informative ergonomic analyzed can contribute to the improvement of the information and consequent visual progress of those, on the labels of chocolate package investigated. As recommendation towards the maker of the product, the outcome of the research indicates: harmonize the proportion of the letters and numbers; enlarge the letters size; make the visual information more comprehensive determined by the reading field; put the expiry date in a better visual place